Status and Mating Success Amongst Visual Artists - Clegg, Helen; Miell, Dorothy; Nettle, Daniel (Frontiers in Psychology, 2011)
Geoffrey Miller has hypothesized that producing artwork functions as a mating display. Here we investigate the relationship between mating success and artistic success in a sample of 236 visual artists. We derived two measures of artistic success, one based on self-perception and the other on more objective variables to do with artistic output and attitudes, as well as a measure of artistic identity. More subjectively successful male artists and those males with a stronger artistic identity had more sexual partners than less successful artists. There was no relationship between mating success and the more objective measure of artistic status. Predicted sex differences in mating success were found for both measures of artistic success and for artistic identity. Male artists with greater self-perceived success had a mating strategy based on longer term relationships. More objective measures of success and identity did not affect mating strategy. This study may provide support for the emerging idea that our evolved psychological predispositions enable humans to construct mechanisms, such as identity, that aid our reproductive success and survival.